Penyusunan Buku Pengayaan Bermuatan Kritik Sosial pada Keterampilan Menulis Teks Anekdot - Nur Azizah, Laila; Febriani, Meina (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
Lack of teaching resources to support learning activities can result in learning objectives not being optimal. Therefore, additional supporting books are needed. Textbooks and non-textbooks are books used in learning. Books that accompany textbooks are enrichment books. Reading, writing, listening and speaking, and watching are aspects of language skills. Indonesian language learning is realized in text-based learning in the form of learning text genres and students must master these language skills. An anecdote is a relatively new text that has appeared. Social criticism is one of the themes in the anecdote. The method used in this research is research development from Borg and Gall. The research methods include: (1) potential and problem analysis, (2) data collection, (3) prototype design, (4) prototype validation, (5) prototype revision, research results in the form of; (1) description of the needs of teachers and students, (2) principles of book development, (3) development of book prototypes, (4) expert assessment, and (5) improvement of book development to enrich skills in writing anecdotal texts containing social criticism.